Auditor Independence in New Zealand: Further Evidence on the Role of Non-Audit Services - Si Wen (Stacey) Wang; David Hay (Journal of Accounting and Management Information Systems (JAMIS), 2013)
Non-audit services provided by auditors to their audit clients continue to be a controversial issue around the world. While research evidence has not usually shown that auditors lose their independence when providing non-audit services, the risk that they could do so is still a concern to regulators and financial report users. However, after changes to the environment of auditing, including new regulation, it may be that the situation has changed. This paper examines whether there is a relationship between non-audit services and the loss of independence for publicly listed New Zealand companies in 2011. The results using three tests – audit fees, audit opinion and auditor tenure – show that there is no impairment of independence with respect to audit fees and auditor tenure. However, there is some evidence of impaired auditor independence in relation to the audit opinion.
Keywords: G18; L84; M41; 650; Auditor Independence; New Zealand; Non-audit Services; Regulatory change